Analysis of excess nitrogen in feeding in the Floating Net Cage in Laut Tawar Lake, Central Aceh - Mainisa Mainisa; Saiful Adhar; Muliani Muliani (Arwana: Jurnal Ilmiah Program Studi Perairan, 2025)
Floating net cage activities produce waste in the form of uneaten feed and metabolic waste that contain nitrogen and phosphorus, which can promote excessive growth of phytoplankton, leading to eutrophication. This research analyzes the excess nitrogen in feed provision in the floating net cage at Laut Tawar Lake. The difference in the amount of N in the feed and the amount of N in the fish represents the amount of N as the excess N in floating net cage activities. Feed samples of 7 different types and fish samples were randomly taken from 3 floating net cage locations, namely One-one, Toweren, and Kebayakan. Based on the results, the average N concentration in the feed used was 6.79% for tilapia and 6.71% for carp. The average N concentration in the tilapia is 7.71±0.61% and in the carp samples is 6.42±1.67%. The tilapia farming contributed N to the waters at a rate of 0.85 kg/m2 over a 4-month, while the carp floating net cage contributed N at a rate of 0.72 kg/m2 over a 5-month. The results indicate that floating net cage activities in Laut Tawar Lake produce N waste to the lake waters amounting to 0.36 kg/m2/month or 11.94 grams/m2/day.